Analysis of the Development of Modern Agritourism Types in West Kazakhstan Oblast - AKTYMBAYEVA, Aliya; NURULY, Yeldar; AKTYMBAYEVA, Bakyt; AIZHOLOVA, Gulzhan (Journal of Environmental Management and Tourism, 2017)
West Kazakhstan Oblast has a decent resource potential and prospects of development of agri-tourism. Agritourism will help to solve such problems in the rural areas of West Kazakhstan like employment, increase income and cultural level of people, markets and infrastructure development of the area. Shaping the opportunities for development and territorial organization of the species agritourism belong to the plant-growing and livestock. In this connection, the authors of this article assesses the opportunities for development and territorial organization of kinds of modern agritourism in the area of plant-growing and livestock production in the context of the administrative districts of West Kazakhstan Oblast. In addition, the identified levels of opportunity for development and territorial organization of agritourism in the West Kazakhstan and levels of capability based on local resource base. Also, the concept of agritourism and its relationship with agriculture, the role of the economy in rural areas in territorial aspect are considered.